Vida, pensamento e obras do professor Júlio Cesar de Mello e Souza - Malba Tahan: o ensino de matemática nas primeiras décadas do século XX - Santos, Anderson Oramísio (2019)
The research seeks to present the importance of Júlio César de Mello e Souza, whose pseudonym is Malba Tahan, for the teaching and learning of Mathematics. The research presents the influences of Malba Tahan for the strengthening and improvement of Mathematics Education, with the discussions and creation of Mathematics in Colégio Pedro II, in 1927, from the I Movimento de Modernização da Matemática in Germany, as well as his participation as professor, author of didactic textbooks during the Francisco Campos Educational Reform in 1931, that was the first initiative of national organization of Brazilian education. Through its set of decrees different degrees and stages of teaching were systematized. Among them, Gustavo Capanema Secondary Education and Educational Reform of 1942, which gave new organization to Secondary Education, creating the four-year gymnasium and the classic and scientific courses of three years. The methodological approach was documentary and bibliographic research. Chervel (1990) defines the first task of the historian of school subjects that is to study explicit content in disciplinary teaching. Thus, for the study of disciplinary contents the researcher benefits from several documents, such as textbooks. The main elements of the research bring a brief history of his life, work and pedagogical discourse, from his birth to world recognition. In order to elucidate the changes in the teaching of Mathematics, in the process of teaching and learning in Mathematics, we chose six didactic manuals authored by Professor Júlio Cesar de Melloe Souza - Malba Tahan and co-authors from the period 1931 to 1942. The purpose was to investigate the guidelines given for the teaching of mathematics in the period of the New School movement and the connection with other areas of knowledge. That represents a possibility to study an important historical stage for the development of school mathematics in Brazil. Another issue is how would the didactic manuals interpret the determinations of the reforms and how the school mathematics of one reform was changed to another. Thus, we can point out that the teacher and writer Júlio César de Mello e Souza suggested the use of technologies in the classroom, the use of the History of Mathematics, the presentation of Recreational Mathematics, Mathematical Games and, mainly the use of situation-problems as a starting point for the introduction of mathematical contents. That provided the reader with a minimum knowledge of the themes addressed by him, which can be a rich motivating tool for the teaching and learning of Mathematics, besides emphasizing its ideas and forms of pedagogical activity.